Genetic characterization and evolutionary inference of TNF-α through computational analysis - Awasthi,Gauri (2008)
TNF-α is an important human cytokine that imparts dualism in malaria pathogenicity. At high dosages, TNF-α is believed to provoke pathogenicity in cerebral malaria; while at lower dosages TNF-α is protective against severe human malaria. In order to understand the human TNF-α gene and to ascertain evolutionary aspects of its dualistic nature for malaria pathogenicity, we characterized this gene in detail in six different mammalian taxa. The avian taxon, Gallus gallus was included in our study, as TNF-α is not present in birds; therefore, a tandemly placed duplicate of TNF-α (LT-α or TNF-β) was included. A comparative study was made of nucleotide length variations, intron and exon sizes and number variations, differential compositions of coding to non-coding bases, etc., to look for similarities/dissimilarities in the TNF-α gene across all seven taxa. A phylogenetic analysis revealed the pattern found in other genes, as humans, chimpanzees and rhesus monkeys were placed in a single clade, and rats and mice in another; the chicken was in a clearly separate branch. We further focused on these three taxa and aligned the amino acid sequences; there were small differences between humans and chimpanzees; both were more different from the rhesus monkey. Further, comparison of coding and non-coding nucleotide length variations and coding to non-coding nucleotide ratio between TNF-α and TNF-β among these three mammalian taxa provided a first-hand indication of the role of the TNF-α gene, but not of TNF-β in the dualistic nature of TNF-α in malaria pathogenicity.